The Effect of Knowledge Sharing and Work Engagement on Teacher Performance with Organizational Citizenship Behavior (OCB) as a Mediating Variable - George Marcus Rahanbinan; Novalien Carolina Lewaherilla; Agusthina Risambessy (Sean Institute, 2026)
This study aims to analyze the influence of knowledge sharing and work engagement on teacher performance with Organizational Citizenship Behavior (OCB) as a mediating variable at the YPPK Dr. JB Sitanala School, Ambon Island Branch. The study used a quantitative approach with a sample of 104 teachers. The analysis was conducted using SmartPLS. The results showed that knowledge sharing and work engagement did not directly affect teacher performance. However, knowledge sharing and work engagement significantly influenced OCB, and OCB significantly influenced teacher performance. OCB was proven to mediate the relationship between knowledge sharing and work engagement on teacher performance. This finding emphasizes the importance of strengthening extra-role behavior in improving teacher performance.